Comparing the Effects of Transcranial Direct Current Stimulation and Cognitive Rehabilitation on Language Skills and Attention in Elderly With Mild Alzheimer\'s Disease - Arezoo Mojarrad; Esmaeil Sadri Damirchi; Ali Sheykholeslami; Ali Rezaii Sharif; Vahid Abbasi (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives Alzheimer's disease (AD) is one of the most common problems in the elderly, which causes a decline in their cognitive function. This study aims to compare the effects of transcranial direct current stimulation (tDCS) and short-term cognitive rehabilitation on language skills and attention in older people with mild AD. Methods & Materials This is a quasi-experimental study with a pre-test/post-test/follow-up design. Participants were 60 people over 65 years of age with mild Alzheimer's referred to a neurologist in 2022, who were selected by a convenience sampling method and were randomly assigned into two experimental groups and one control group (20 in each group). Then, the tDCS was applied in one experimental group at 10 sessions of 20 minutes once a week and the short-term cognitive rehabilitation program was provided to the second experimental group at 9 sessions of 90 minutes, once a week. No intervention was provided to the control group. Before, one week after (post-test) and one month after (follow-up) the end of the intervention, the assessments were conducted in all groups using Addenbrooke's cognitive examination- revised (ACE-R). For data analysis, repeated measures analysis of variance test was used in SPSS software, version 23. Results Both methods improved the writing and naming domains of language skills, but they had no significant effect on the attention variable.  Conclusion Both tDCS and short-term cognitive rehabilitation can be used to improve the language skills of older adults with mild AD.